Сorrection of Corneal Astigmatism in Patients with a Thin Cornea by Improved Combined Technology - M. S. Stroyko; S. V. Kostenev; A. L. Pakhomova (Oftalʹmologiâ)
Purpose: to carry out an advanced combined technology, including femtosecond astigmatic keratotomy and topographically-oriented photorefractive keratectomy in order to correct corneal astmigmatism in patients with a thin cornea. Presentation and evaluation of the results of this observation.Patients and methods. There are data of 19 patients (30 eyes) with complex myopic astigmatism combined with a thin cornea who received the operation of femtosecond astigmatic keratotomy (the first stage of an improved combined technology). Mean values before surgery: sph –4.1 ± 2.1 (from –0.3 to –7.8) D, cyl –4.9 ± 1.4 (–3.0 to –7.3) D, UDVA 0.1 ± 0.05 (from 0.01 to 0.2) of the rows of table, CDVA 0.6 ± 0.1 (from 0.4 to 0.9) of the rows of table, Kmax 46.70 ± 1.1 (from 44.50 to 48.50), Kmin 42.8 ± 1.3 (from 40.00 to 44.00), the thickness of the cornea is 470.0 ± 12.7 (from 4470 to 495.0) μm. The second stage: topographically oriented photorefractive keratectomy was performed to the same patients with the aim of correcting residual ametropy. Mean values before surgery: sph –5.3 ± 2.0 (from –1.8 to –8.8) D, cyl –1.6 ± 0.8 (from –0.5 to –3.0) D, UDVA 0.3 ± 0.1 (from 0.1 to 0.6) rows of the table, CDVA 0.7 ± 0.1 (from 0.5 to 0.9) rows of the table, Kmax 46.70 ± 1.1 (from 44.50 to 48.50), Kmin 42.8 ± 1.3 (from 40.00 to 44.00), the thickness of the cornea 464.3 ± 8.3 (from 460.0 to 485.0). All patients from the study received a diagnostic examination by standard and special methods based on the S. Fyodorov Eye Microsurgery State Institution, a screening of the keratoconus on the scanning topograph Pentacam HR “Oculus Optikgerate GmbH”, Germany was carried out. The first stage of the advanced combined technology was used the LenSx Laser (“Alcon”, USA), the second stage — WaveLight EX-500 (“Alcon”, USA), was used.Results. After the completion of two stages of improved combined technology the following results were obtained: reduction of the sph with –4.1 ± 2.1 (from –7.8 to –0.3) to –0.4 ± 0.3 (from –1.0 to 0.0), cyl with –4.9 ± 1.4 (from –7.3 to –3.0) to –0.1 ± 0.1 (from –0.5 to 0.0), Kmax from 44.70 ± 1.1 (from 44.50 to 48.50) to 37.8 ± 1.6 (from 36.00 to 43.00), Kmin 42.80 ± 1.3 (from 40.00 to 44.00) to 37.00 ± 1.3 (from 36.00 to 40.00), CDVA growth with 0.6 ± 0.l (from 0.4 to 0.9) to 0.8 ± 0.1 (from 0.5 to 1.0), UDVA from 0.1 ± 0.05 (from 0.01 to 0.2) to 0.7 ± 0.1 (from 0.4 to 0.9).Conclusion. The improved combining technology, including femtosecond astigmatic keratotomy and topographically — oriented photorefractive keratectomy is effective and safety technology, allowing to correct of corneal astigmatism in patients with a thin cornea.